Comparative Analysis of CMOS Transmission Gate Based Adders (International Journal of Engineering and Computer Science, 2017)
The adder is the most commonly used arithmetic block of the Central Processing Unit (CPU) and Digital Signal Processing (DSP), therefore its performance and power optimization is of utmost importance. In realizing modern Very Large Scale Integration (VLSI) circuits, low-power and high-speed are the two predominant factors which need to be considered. There always exists a trade-off between the design parameters such as speed, power consumption, and area We designed three different types of 4-bit transmission gate based adders namely Ripple Carry Adder, Carry Select Adder and Carry Lookahead Adder We compared the different adders on basis of no. of transistors, the average power consumption and delay. The simulation results are taken for 180nm technology with the help of Tanner (T-spice) simulation tool.